A study of thermoelastic damping in micromechanical resonators under unified generalized thermoelasticity formulation. (June 2019) - Kumar, Roushan; Kumar, Ravi
In this article, a unified formulation for the generalized coupled thermoelasticity theories by employing an appropriate system of partial differential equations as the governing system is presented to investigate thermoelastic damping of a microbeam resonator. The generalized coupled thermoelasticity theories namely: the extended thermoelasticity proposed by Lord and Shulman, the thermoelasticity without energy dissipation (thermoelasticity type-II) and the thermoelasticity with energy dissipation (thermoelasticity type III) in a unified way by introducing the unified parameters. An explicit formula of thermoelastic damping has been derived in a unified way and numerical results for effects of the beam height, relaxation time parameter on thermoelastic damping of the microbeam resonator have been studied and compared.